Gland New Psychosis: New Onset Adult Psychosis with Suicidal Ideation and Attempt in the Setting of Thyroid Storm - Esteban Cota; Jacob Lentz (Case Reports in Psychiatry)
We present a case of new onset psychosis in the setting of thyroid storm in a woman with no previous psychiatric history. The patient presented with ongoing suicidal ideation, a suicide attempt that was interrupted by her husband, and audio and visual hallucinations. The patient was placed on a psychiatric hold and treated for thyrotoxicosis as well as psychosis. Treatment of the thyroid hormone overload resulted in a rapid resolution of her symptoms; she was discharged in excellent condition, and she has had no repeat hallucinations or self-injury ideation or attempts since. Although rare, thyrotoxicosis is a potentially life-threatening cause of psychiatric illness and should always be kept on the differential diagnosis for a patient with a first episode of psychosis. This case highlights how thyroid storm physiology, beyond its well-studied hemodynamic and metabolic instability, can be potentially fatal due to psychiatric sequelae. It also highlights the crucial role of a thorough history and physical exam in all patients.